Collaborative Regulation and Supply Chain Resilience of Halal Pharmaceuticals in Malaysia - AIGBOGUN, OSARO (2018)
Resilience is the vital feature of supply chains, that confer on it the ability to withstand the adverse effects of disruptive events. Most of the previous studies on supply chain resilience in general, and in the context of the halal industry, including pharmaceuticals have been conceptual, theoretical, normative, or at best qualitative in approach, concentrating on identifying the elements of resilience.